2002
DOI: 10.1080/00926230252851294
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Female Patients with Sexual Dysfunction Who Also Had A History of Blunt Perineal Trauma

Abstract: Perineal trauma can occur in both genders, however, data supporting the relationship between sexual dysfunction and blunt perineal trauma in women is lacking. This study reviewed the patient characteristics of women with sexual dysfunction who also had a history of blunt perineal trauma. A neurogenic form of sexual dysfunction has been implicated, with primary complaints of orgasm disorder and abnormalities noted on genital sensory testing. Further research in this area is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…Although perineal trauma occurs in both genders, data supporting the association between sexual dysfunction and blunt perineal trauma in women are lacking. A study that looked at the patient characteristics of women with sexual dysfunction that had undergone blunt perineal trauma implicated a neurogenic form of sexual dysfunction, with primary complaints of orgasmic disorders and abnormalities on genital sensory testing [61]. In another publication the same authors reported three cases of post-traumatic clitoral neuropathy and neuralgia resulting from trauma to the genitalia.…”
Section: Specific Disorders Affecting Sexual Dysfunctionmentioning
confidence: 99%
“…Although perineal trauma occurs in both genders, data supporting the association between sexual dysfunction and blunt perineal trauma in women are lacking. A study that looked at the patient characteristics of women with sexual dysfunction that had undergone blunt perineal trauma implicated a neurogenic form of sexual dysfunction, with primary complaints of orgasmic disorders and abnormalities on genital sensory testing [61]. In another publication the same authors reported three cases of post-traumatic clitoral neuropathy and neuralgia resulting from trauma to the genitalia.…”
Section: Specific Disorders Affecting Sexual Dysfunctionmentioning
confidence: 99%
“…Work by Munarriz et al. also suggests that pudendal nerve insults may occur following an incidental trauma during cycling [29]. These authors reported that 77% of bicycle injury cases were caused by incidental pelvic floor trauma, most commonly involving the crossbar.…”
Section: Resultsmentioning
confidence: 98%
“…Apesar do enorme avanço tecnológico observado nos últimos anos, incluindo o aprimoramento de exames subsidiários como a ultra-sonografia, a tomografia computadorizada e a radiologia intervencionista, não sendo estes isentos de resultados falso-negativos, o exame físico em momento algum deverá ser esquecido 4 .…”
Section: Cláudiounclassified